Exploring the effects of socio-economic inequalities on health and disability in Northern Irish adolescents: evidence from a nationally representative longitudinal study. (1st January 2023) - McElroy, Eoin; Courtney, Caroline; Adamson, Gary; Taggart, Laurence; Mulhall, Peter; Ferry, Finola; Murphy, Jamie; O'Connor Bones, Una
Abstract : Although a negative association between socio-economic inequalities and health has been established, there is a dearth of robust longitudinal studies examining this relationship in adolescents. This study used a large, nationally representative longitudinal data set to investigate the association between socio-economic inequality, subjective health status and disabilities among young people in Northern Ireland over a ten-year period. Data were from the Northern Ireland Longitudinal Study, a census-based record linkage study (N = 46, 535). Logistic regression models were estimated in which health and disability variables from the 2011 census were predicted by household deprivation in education, housing quality, housing tenure and employment from the 2001 census. Models were adjusted for health and disability status in 2001. Deprivation in employment, housing tenure and coming from a single-parent household in 2001 independently predicted poorer subjective health and disability status ten years later [ORs = 1.28–1.93]. Deprivation in education in 2001 was also associated with increased risk of disability in 2011 [OR = 1.15; 95% CI = 1.06–1.25]. These results show that there is a need to dedicate more resources and support for economically disadvantaged children and young people in Northern Ireland, where child health outcomes are poorer than in the rest of the UK.